Outcomes of hematopoietic stem cell transplantation in patients with SARS-CoV-2 infection during the Omicron era - Won Jun Choi; Jinhong Lee; Kowoon Choi; Dong Mi Kim; Nayoung Han; Jin-Ho Choi; Jongheon Jung; Hyewon Lee; Jun Yong Choi; Young Ju Choi; Hyeon-Seok Eom; June Young Chun; et al. (International Journal of Infectious Diseases, 2024)
Here, we present the outcomes of four patients with COVID-19 who underwent hematopoietic stem cell transplantation (HSCT) at the National Cancer Center in South Korea. Despite concerns about the unfavorable course of COVID-19 in HSCT recipients, none of our patients experienced severe COVID-19. Moreover, extended viral shedding in case 1, lasting over 100 days, was resolved after successful engraftment. Contracting the virus when the host could not mount enough of an immune reaction might result in a paradoxically favorable course. Vaccination, monoclonal antibodies, and antiviral agent usage against COVID-19 might also be effective. We suggest, if necessary, HSCT should not be deferred in COVID-19 patients.